Discovery of N-cyclobutylaminoethoxyisoxazole derivatives as novel sigma-1 receptor ligands with neurite outgrowth efficacy in cells. Issue 13 (14th February 2018) - Sun, Hao; Wang, Yun-Jie; Shi, Wen-Wen; Yang, Fan; Tang, Jie; Pang, Tao; Yu, Li-Fang
Abstract : Herein we reported a series of 14 novel derivatives based on the N -cyclobutylaminoethoxyisoxazole scaffold. Abstract : Herein we reported a series of 14 novel derivatives based on the N -cyclobutylaminoethoxyisoxazole scaffold. In vitro binding studies of these compounds demonstrated their low nanomolar to subnanomolar potencies as σ1 receptor ligands, with moderate to excellent selectivity over the σ2 receptor as represented by compounds17–30 . The majority of the derivatives scored high (>4.7) in the CNS MPO appraisal system, indicating their high likelihood in penetrating the blood–brain barrier. A number of these compounds exhibited significant neurite outgrowth efficacy in N1E-115 neuronal cells and displayed excellent selectivity for σ1 receptors over the selected endogenous neurotransmitter transporters, such as DAT, NET and SERT. Among the mini-series, compound28 ( K i σ1 = 0.2 nM, K i σ2 = 198 nM, CNS MPO score = 5.4) emerged as a promising selective σ1 receptor ligand that warrants its further evaluation as a potential therapeutic for neurodegenerative diseases.